Development of the JARE deep ice coring system (II) - Hideki Narita; Yoshiyuki Fujii; Akiyoshi Takahashi; Yoichi Tanaka; Hideaki Motoyama; Kunio Shinbori; Morihiro Miyahara; Nobuhiko Azuma; Yoshiki Nakayama; Okitsugu Watanabe (Antarctic Record, 1995)
A deep ice coring system, which is to be used at Dome Fuji Station located at the summit of the Queen Maud Land ice sheet in 1995 and 1996,has been under development since 1988. The mechanical system was designed to reduce power consumption and weight. Many experiments were carried out on parts of the system in a cold laboratory. Simultaneously, field experiments of the drill system were done at Dome GRIP, Greenland ice sheet and at Rikubetsu, Hokkaido. As a result, a electro-mechanical drill which is simple both in shape and mechanism can be designed and produced incorporating many new ideas introduced through the experiments.